Acquired Rectourethral and Rectovaginal Fistulas in Children: A Systematic Review - Huang, Xinjie; Tan, Sarah Siyin; Chen, Yajun; Li, Tian (Frontiers in Pediatrics, 2021)
Background Acquired rectourethral (RUF) or rectovaginal fistulas (RVF) in children are rare conditions in pediatric surgery. Prior literature are retrospective studies and based on a small number of patients. The managements and outcomes vary widely across different studies. No standard or recommended management has been universally adopted. The goal was to systematically summarize different causes, provide an overlook of current clinical trend and to derive recommendation from the literature regarding the etiology, managements, and outcomes of pediatric acquired RUF and RVF. Methods PubMed, Embase, Cochrane databases were searched using terms: rectourethral fistula, recto-urethral fistula, urethrorectal fistula, urethro-rectal fistula, rectovaginal fistula. All studies were retrospective, in English, and included patients under the age of 18 years. Any series with congenital cases, adult (>18 years), <2 fistula cases less and obstetric related causes were excluded. The PRISMA guideline was followed. Results Of the 531 records identified, 26 articles with 163 patients (63 RUF and 100RVF) were fully analyzed. Most RUF resulted from trauma, most RVF were from infection of HIV. About 92 patients underwent 1 of 3 categories of definitive repair, including transanal (4.3%), trans-sphincteric (48.9%) and transperineal (30.4%). Tissue interposition flaps were used in 37.6% patients, while temporary fecal diversions were used in 63.9% patients. Fistula was successfully closed in 50.3% patients (98.4% RUF and 20% RVF). 89.1% and 79.7 % of surgical repair patients had optimal fecal and urinary functions respectively. In the inflammatory bowel disease and HIV infection related RVF patient group, the closure rate was prohibitive poor. Conclusions Most RVF are a sign of systematic diseases like HIV-infection or IBD and are associated with poor general conditions. While conservative treatment is recommended, stable patients can benefit from surgery. Further investigation is recommended if RVF are encountered without trauma or surgical history. RUF are likely to result from trauma or surgery, and transperineal or trans-sphincter approach can lead to closure and optimal function results. Fecal diversion and/or urinary diversion are helpful in some cases, while interposition technique may not be necessary. An objective scoring system for long-term follow-up and reporting consensus is needed to address treatment inconsistence.